2023
DOI: 10.1186/s12888-022-04512-y
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the impact of mental health conditions on vaccine uptake in high-income countries: a systematic review

Abstract: Background Vaccination is an essential public health intervention to reduce morbidity and mortality from infectious diseases. Despite being at higher at risk of infectious diseases, health inequalities towards vaccine uptake in people with mental health issues have not been systematically appraised. Methods We searched 7 databases from 1994 to 26/03/2021. We included all studies with a relative measure of effect comparing a group with a mental heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Vaccination is a pivotal public health intervention, substantially reducing morbidity and mortality associated with infectious diseases [ 1 , 2 , 3 ]. Immunization programs have contributed to a significant decline in the global burden of vaccine-preventable diseases, thus enhancing millions of individuals’ overall quality of life [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Vaccination is a pivotal public health intervention, substantially reducing morbidity and mortality associated with infectious diseases [ 1 , 2 , 3 ]. Immunization programs have contributed to a significant decline in the global burden of vaccine-preventable diseases, thus enhancing millions of individuals’ overall quality of life [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous systematic reviews exploring the association between mental illness and uptake of various vaccinations have reported heterogenous results. (8, 9) Similarly, results from previous country-specific studies of COVID-19 vaccination uptake in people with mental illness have been inconsistent. While some studies have observed significantly lower uptake of COVID-19 vaccination among individuals with mental illness,(10, 11) others have either reported higher uptake (12), no significant difference,(13) or differences in uptake according to the type of mental illness.…”
Section: Introductionmentioning
confidence: 99%
“…Immunization is a cornerstone in public health, pivotal in diminishing the prevalence and severity of infectious diseases and their effects on health outcomes [ 1 , 2 , 3 ]. Vaccine-preventable diseases remain a significant public health concern globally.…”
Section: Introductionmentioning
confidence: 99%